DDIS-13. UNDERSTANDING GLIOBLASTOMA SUSCEPTIBILITY TO TOP2-TARGETING DRUGS FOR PERSONALIZED THERAPY. (5th November 2018) - Awah, Chidiebere; Gonzalez-Buendía, Edgar; Zhao, Junfei; Feldstein, Eric; Chen, Li; Mahajan, Aayushi; Warnke, Louisa; Wang, Lu; Park, Cheol; Winter, Jan; Konermann, Silvana; Shilatifard, Ali; et al.
Abstract: Poor outcomes in glioblastoma are partially explained by unpredictable individual responses to therapy. Topoisomerase II (TOP2) poisons Etoposide and Doxorubicin, which induce double-strand DNA breaks, are effective for some glioblastoma lines. On the other hand, the TOP2-enzymatic inhibitor MST16 is used for lymphomas, but has not been tested for glioblastoma. We investigated biomarkers for glioblastoma susceptibility to these drugs to repurpose them with a precision medicine approach. We performed a genome-scale CRISPR knockout (KO) screen on an Etoposide-susceptible cell line using this drug to select resistant clones. The screen identified 106 genes from DNA damage response, a pathway that was over-represented among genes involved in etoposide susceptibility. We overlapped genes whose loss confers Etoposide resistance from our screen with genes whose expression correlates with susceptibility to this drug across 35 glioma cell lines. This approach elucidated 6 genes, including some that regulate protein synthesis, as TOP2 poison biomarker candidates. Validation through CRISPR KO of several of these confirmed that their loss confers resistance to Etoposide and Doxorubicin, and their protein levels were predictive for TOP2 poison susceptibility across glioma cell lines. In contrast, these biomarkers were not predictive of glioma response to TOP2-inhibitor drug MST-16. Through ChIP-seq, we discovered that TOP2B binding coincides with open chromatin in promoters of PDGFRA. Moreover, TOP2 inhibition with MST-16 downregulated this gene. Baseline expression of PDGFRA across glioma cell lines was highly predictive of MST-16 susceptibility, which was confirmed in an independent dataset of patient-derived glioma xenograft lines. Using complementary unbiased approaches, we identified several novel biomarkers for personalizing TOP2-targeting therapy for this disease. Inter-individual differences in glioblastoma susceptibility to TOP2 poisons relates to protein synthesis and DNA damage, whereas susceptibility to TOP2 inhibitors relates to TOP2B-mediated transcriptional regulation of an oncogene.